Using contactless mobile payment in the Vietnamese restaurant industry - Charalampos Giousmpasoglou; Dzung Dinh (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: Contactless Mobile Payment (CMP) is a technological innovation that shapes the future of service-related industries. This study develops a critical understanding of CMP in the context of consumer behaviour and explores its use in the Vietnamese restaurant industry. Methods: An online survey was used to collect the data (n=153) from Vietnamese consumers. Data analysis was conducted with the use of SPSS and AMOS software. A Confirmatory Factor Analysis (CFA) in conjunction with Structural Equation Modelling (SEM) were employed to explore consumer perceptions regarding the use of CMP. Results: The findings indicate that consumers find CMP a fast and convenient way to make transactions in Vietnamese restaurants. The findings also indicate the importance of ease of use and security. Implications: The study contributes to the understanding of consumer behaviour in regard to technology in the service industries context focused on the restaurant industry. The managerial implications of this study highlight a number of benefits for both consumers and businesses, such as efficiency, speed, and improved customer service; on the other hand, the potential of fraud poses a serious threat for both sides.
Keywords: L83; N35; N7; 330; Consumer Behaviour; Contactless Mobile Payment; Restaurant Industry